Micronutrientes em cultivares de gérbera de vaso - Ludwig, Fernanda [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Mota, Poliana Rocha D'Almeida [UNESP]; Bôas, Roberto Lyra Villas [UNESP] (Lepidus Tecnologia, 2012)
The present work aimed at evaluating the contents and accumulation in four different gerbera cultivars subjected to fertigation with two nutritive solutions. The experiment was carried out in a greenhouse, from May to July 2006, at DNR, Soil Science Sector, Agronomical Sciences College, UNESP, Botucatu, São Paulo State. The experiment was installed in randomized blocks and constituted of a 4x2 factorial scheme, being four gerbera cultivars (Cherry, Golden Yellow, Salmon Rose and Orange) and two concentrations of nutritive solution (S1-50% and S2-100%), corresponding to the electrical conductivity of 0,92 and 1,76 dS m-1, during the vegetative period and 1,07 and 2,04 dS m-1, during the reproductive one. By the end of the vegetative (41 DAA) and reproductive (62 DAA) periods, were quantified the contents and accumulation of the micronutrients in vegetal tissue. The nutrients demands had been differentiated between the cultivars, smaller to Orange (59 mg kg‑1 B, 5 mg kg‑1 Cu, 180 mg kg‑1 Fe, 46 mg kg‑1 Mn, at the end of cycle). The supply of nutrient solution more concentrated reflected in a higher content of micronutrient in the tissue. The greatest accumulations had been registered at the reprodutive period, presentig the following order of absortion Fe>Mn>B>Zn>Cu (237, 72, 71, 30 e 6 µg plant-1).

O presente trabalho foi conduzido com o objetivo de avaliar o teor e o acúmulo de micronutrientes em quatro cultivares de gérbera fertirrigadas com duas soluções nutritivas. O experimento foi conduzido em casa de vegetação de maio a julho de 2006 no DRN/Ciência do Solo na FCA, Unesp, município de Botucatu/SP, Brasil. O delineamento experimental utilizado foi o de blocos casualizados, constituído de fatorial 4x2, sendo quatro cultivares de gérbera (Cherry, Golden Yellow, Salmon Rose e Orange) e duas concentrações de solução nutritiva (S1- 50% e S2- 100%). Ao final dos períodos vegetativo (41 DAA) e reprodutivo (62 DAA), foram quantificados o teor e o acúmulo dos micronutrientes no tecido vegetal da parte aérea. A cultivar Orange acumulou menor quantidade de micronutrientes (59 mg kg‑1 B, 5 mg kg‑1 Cu, 180 mg kg‑1 Fe, 46 mg kg‑1 Mn, ao final do ciclo) em relação às demais cultivares. O fornecimento da solução nutritiva mais concentrada se refletiu em maior teor dos micronutrientes no tecido. O maior acúmulo foi registrado no período reprodutivo, apresentando a seguinte ordem de absorção: Fe>Mn>B>Zn>Cu (237, 72, 71, 30 e 6 µg planta-1).
Micronutrients in potted gerbera cultivars
Keywords: Gerbera jamesonii; Plant nutrition; Fertigation; Gerbera jamesonii; Nutrição de plantas; Fertirrigação